Processo al processo canonico di nullità matrimoniale - Mondin, Paolo Buselli (Ius ecclesiae, 2015)
The marriage nullity process is an institute that is sometimes misunderstood. It is not only that mere contradictions underlie this lack of comprehension, but there are also pressing expectations that the process will be seen as an educational context. That is, it is seen as an opportunity for the faithful to be able to understand, from the sentences that are issued, the deeper significance of the failure of their marriage and also the (self-transcendent) meaning of their very Christian identity. These considerations can therefore become a useful impetus for thinking of the process as a place for dialogue between psychology and religion, where spirituality and affectivity on the one hand and the bona matrimonialia and the structure of relationships on the other hand are not considered mutually opposed but integrated with one another and mutually enriching. The very deontology of ministers of justice could be improved in a highly functional manner by the intrinsic educational demands of matrimonial trials